Bioactive Substances, Heavy Metals, and Antioxidant Activity in Whole Fruit, Peel, and Pulp of Citrus Fruits - Anna Czech; Agnieszka Malik; Bożena Sosnowska; Piotr Domaradzki (International Journal of Food Science)
The use of whole citrus fruits in the food industry means that the valuable peel is used, but this may raise palatability or health concerns among consumers. The content of sugars, dietary fibre, redox compounds, lead, and cadmium was compared in citrus fruits (orange; pomelo; mandarin; lemon; key lime; and red, yellow, and green grapefruit). The pulp of all fruits contained significantly less fibre, tannins, and phenolic compounds than the peel. Whole citrus fruits had significantly lower content of sugars and higher content of dietary fibre and phenolic compounds, including ferulic acid, than their pulps. Whole grapefruits had higher concentrations of ascorbic acid. Whole lemons, limes, and mandarins had higher antioxidant potential than their pulp, due to their higher content of ascorbic acid, tannins, and phenolic compounds. Lead and cadmium content in whole fruits, while higher than in the pulps, was well below the acceptable daily intake.